PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN SOFTWARE GEOGEBRA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VIII SMPN 30 PADANG - Riztavia, Nurul Syifa (Jurnal Edukasi dan Penelitian Matematika, 2024)
To determine how well learning goals have been met, learning outcomes are essential. Class VIII students at SMPN 30 Padang continue to have less-than-ideal academic performance, nonetheless. The purpose of this research is to find out how eighth graders at SMPN 30 Padang fared academically in mathematics when taught using the Geogebra program and the Discovery Learning instructional paradigm. This study is a quasi-experimental design with a control group that only received the posttest. Students from SMPN 30 Padang in the eighth grade made up the study's population. A basic random selection process was used to select the sample classes, which are VIII A and VIII D. The research tool used was an evaluation of students' final mathematical performance. A comparison of the experimental and control classes' final exam scores showed that the former averaged 72.8 and the latter 64.5. At a significance level of α = 0.05, the t-test data analysis of the final test results produced a P-value of 0.017. It follows that eighth graders at SMPN 30 Padang who use the Geogebra program in conjunction with the Discovery Learning concept outperform their peers who follow a more traditional classroom approach.Keywords–  learning outcomes, Discovery Learning, Geogebra